Concurrence of Crimes under Ethiopian Law: General Principles vis-à-vis Tax Law - Leake Mekonen Tesfay (Mizan law review, 2023)
One or successive act(s) may lead to multiple criminality. According to the principle of unity of guilt and penalty, however, one provision punishes the combination of acts flowing from a single criminal guilt. This principle applies to crimes in Ethiopia’s Criminal Code and in special penal legislations, unless otherwise provided. This article examines the application of general criminal law provisions to special penal legislations, using tax crimes as illustration. The author argues that the tax legislations do not have, and do not need, special rules on concurrence of crimes. Except for acts committed in different tax periods with renewed criminal guilt, tax evasion is the major offence and prosecution/conviction for other predicate offences should be considered only where the evidence is deficient to prove tax evasion. The author also argues that enacting penal law is the power of the Federal Government and regional states may penalize only matters not covered by the federal penal law. This, as a rule, precludes concurrent criminal liability for a single act based on federal and state laws. However, in the context of separate federal and state taxation powers, a single act may simultaneously violate federal and state tax laws.